2022
DOI: 10.20944/preprints202209.0334.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers and Recommendations for a Cervical Cancer Screening Program among Women in Low-resource Settings in Lagos Nigeria: A Qualitative Study

Abstract: Background: Cervical cancer is the fourth most common cancer in women globally despite being a largely treatable and preventable malignancy. Developing countries account for over 80% of all new cases of cervical cancer. Women residing in low-resource settings such as those residing in slums have a higher risk of cervical cancer, and lower uptake of cervical cancer screening. Diverse barriers influence the uptake of cervical cancer screening among women in low-resource settings. Objectives: This qualitative stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Findings from this study have revealed good knowledge, poor attitude towards CC screening and vaccination, and a low level of uptake of CC screening and vaccination. This is contrary to the study by Olubodun et al (2019) among women residing in an urban slum in Lagos, Nigeria, where knowledge about cervical cancer screening and vaccination was poor, and attitude was exemplary. This observed difference in knowledge and attitude may be due to the variance in the sociodemographics of the participants in the two studies.…”
Section: Discussion Of Findingscontrasting
confidence: 95%
“…Findings from this study have revealed good knowledge, poor attitude towards CC screening and vaccination, and a low level of uptake of CC screening and vaccination. This is contrary to the study by Olubodun et al (2019) among women residing in an urban slum in Lagos, Nigeria, where knowledge about cervical cancer screening and vaccination was poor, and attitude was exemplary. This observed difference in knowledge and attitude may be due to the variance in the sociodemographics of the participants in the two studies.…”
Section: Discussion Of Findingscontrasting
confidence: 95%
“…In a communitybased study in Elmina, Ghana, uptake was only 0.8% [12] and 6% in a Kenyan study [13]. This low uptake of screening services has also been highlighted by studies in Nigeria, ranging from 0% screening as reported by Balogun et al 2012 [14] and Igwilo et al 2012 [15] in Lagos and Edo states respectively, 0.7% screening in another study in Lagos [16], and 5% pap smear uptake by respondents in a Lagos study [17]. Similarly, in a study in Onitsha, a metropolitan city in Anambra, Southeast Nigeria, only 1.8% of respondents had done a cervical screening test [18].…”
Section: Introductionmentioning
confidence: 77%
“…Human Papillomavirus (HPV) and HPV vaccines across different population segments. In Nigeria, these gaps were observed among high school students, men, women residing in urban slums, urban and rural areas [6,9,10,18,19]. This widespread lack of awareness and inadequate knowledge across diverse groups calls for concerted efforts to bridge the informational gap across population groups.…”
Section: Our Study's Findings On Knowledge Resonated With Previous Re...mentioning
confidence: 99%
“…Mothers play a pivotal role in this context, as their understanding and beliefs about HPV and its vaccines significantly impact the vaccination choices for their children. However, despite instances where there's a strong willingness to vaccinate, the actual uptake of the HPV vaccine often remains low [9].…”
Section: Introductionmentioning
confidence: 99%